Sports Nutrition - Current Recommendations - König D; Carlsohn A; Braun H; Großhauser M; Lampen A; Mosler S; Nieß A; Schäbethal K; Schek A; Stehle P; Virmani K; Ziegenhagen R; et al. (Deutsche Zeitschrift für Sportmedizin)
Adequate intake of high quality proteins and amino acids is essential for the body in order to build up structures such as muscle, tendons, ligaments and bone. Protein intake also regulates and affects various metabolic processes, including hormonal regulation. Accordingly, proteins and amino acids are, to varying extents, able to stimulate or inhibit anabolic signal transduction pathways and the synthesis and secretion of various hormones such as insulin, growth hormone and insulin-like growth factor 1 (IGF-1).This means that tailoring protein intake to an athletes specific type of sport and exercise intensity can be helpful in supporting the training process and improving performance. The aims of adjusting intake in this way may include maintaining or building muscle mass or muscle strength, preventing a catabolic state, and improving recovery following exercise.Even though the importance of protein intake in the field of sport is increasingly well-known, there is still much controversy regarding intake levels, types of protein sources, optimal amino acid composition, and ideal timing of intake. The lay press and commercial websites in particular often provide biased or incorrect recommendations without scientific evidence.This position paper summarizes the current state of knowledge regarding the physiological effects of protein intake in sports, paying particular attention to the aspects of intake level and the dose-response relationship. Key Words: Metabolic Processes, Amino Acids, Muscle, Dose-Response Relationship, Performance, Regeneration